Increasing Environmental Awareness and Knowledge of the Coastal Community of Karang Panas Beach Ampenan: Peningkatan Kesadaran dan Pengetahuan Lingkungan Masyarakat Pesisir Pantai Karang Panas, Ampenan - Helmi Maulia Nara Hasanah; Lalu Annual Aji Sukma; Maulidealova Dafitri; Sri Maulina Ulfa; Endang Kurniawati (Yayasan Siti Widhatul Faeha, 2026)
The coastal area of Karang Panas Beach Ampenan faces the threat of environmental degradation due to low public awareness and high accumulation of plastic waste. This service activity aims to increase the cognitive knowledge and ecological awareness of the community related to independent waste management and coastal sustainability. The program was implemented using a participatory approach involving 45 residents (fishermen, traders, and local youth). The implementation methods include interactive environmental education, beach cleanup actions, and the procurement of hygiene facilities, which are evaluated using pre-test and post-test questionnaire instruments. The results of the activity showed a drastic increase in participants' understanding from an average score of 45.2% to 85.6%. In addition, participatory action managed to collect 125.6 kg of waste dominated by single-use plastics (62.5%), triggering a real commitment of residents to change waste disposal behavior. In conclusion, participatory-based environmental education is very effective in shaping environmentally conscious behavior in coastal communities. The sustainability of a clean coastal ecosystem requires continuous education programs, the provision of adequate waste management infrastructure, and strong synergy between communities and local governments.